PENGARUH LIFE SKILL PENCAK SILAT TERHADAP MOTIVASI BERPRESTASI WARGA BELAJAR PERGURUAN SILAT WALET PUTI DI KOTA PEKANBARU - Saputra, Bayu; Natuna, Daeng Ayub; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect of pencak silat life skills on the motivation of citizens learning to walet puti college in the city of Pekanbaru. The formulation of the problem in this study is whether there is an influence on the life skills of pencak silat residents learning the Swallow Silat college in the city of Pekanbaru on achievement motivation? This study consists of 2 variables, namely Life Skill (X) and Achievement Motivation (Y) variables, where each variable has 4 variables each. The population in this study were 115 people. The sample of this study used a proportional stratified random sampling technique, which is sampling used when members of the population are not homogeneous consisting of homogeneous groups or proportional strata (Sugiyono, 2011: 93). Data collection techniques in this study were questionnaire techniques, which amounted to 35 statements for the Life Skill variable (X) and 37 statements for the Achievement Motivation variable (Y). Data obtained from respondents totaling 20 people for the trial sample and 75 people for the study sample. After the questionnaire was tested, there were each 4 invalid statements on each variable, and the researcher discarded invalid statements. Based on the average results of the mean value for the variable of achievement motivation of citizens learning silat puti college in the city of Pekanbaru is classified as high, with a mean of 4.34 and SD 0.85 and the life skill variable is also relatively high with a mean value of 4.29 and SD 0, 89. The interpretations obtained for each indicator of achievement motivation and life skills of citizens learning the Swiftlet Silat college in the city of Pekanbaru are all classified as high. Even though the results are moderate, one can still see the high average results. So, seen the most dominant of these 8 indicators is the alignment of learning activities to develop themselves, learning, independent business and joint effort.Key Words: Life Skill, Motivation Achievement Learning Citizens, Pencak